Contribuição da consciência fonológica e das correspondências grafofônicas no desenvolvimento da leitura - Feitoza, Jussara Maria Morais (2018)
This research aims to investigate the contribution of techniques of the phonics method to stimulate phonological awareness in order to facilitate the acquisition of graphophone relations and, consequently, to provide the development of reading skills in 3rd and 4th year students of elementary school I The main hypothesis is that the use of techniques of the phonic method, if used in mediations during reading teaching, can be effective in helping students to associate sounds with spelling, to decode words and even pseudowords. The objective is to elaborate and evaluate a didactic proposal of activities that can contribute to the development of phonological awareness in order to assist in reading learning. This study is based on neuroscience research in the reading process, teaching with the phonics method and intervention with activities that favor the formation of phonological awareness and facilitate the association of graphophonic rules. We analyzed data from twenty-one students distributed in five classes of the third and fourth year of elementary school. Students took a reading test and a phonological awareness test. Then the students of the first group participated in the mediations to form the phonological awareness and in the second group, the mediations helped in the formation of the phonological awareness and association of the gramophone rules. In the third group, also called the control group, the pre-tests and post-tests were compared without applying the aforementioned mediations. At the end of the interventions, the tests were reapplied and analyzed.